2015
DOI: 10.1007/s40265-015-0443-5
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Approach to the Management of Radiation-Induced Hemorrhagic Cystitis

Abstract: Radiation-induced hemorrhagic cystitis (HC) is a complication of pelvic radiotherapy, mainly for prostate and uterine cancers. In the acute phase, patients feel urinary urgency and bladder pain. This phase is reversible after radiotherapy. In the chronic stage, an irritative syndrome is coupled with hematuria during the 2-10 years following radiotherapy. Cystoscopy shows white and frosted mucosa with telangiectasia. The incidence is estimated at 5 % or less. It is suggested that the radiation oncologist review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
32

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 83 publications
(86 reference statements)
0
20
0
32
Order By: Relevance
“…Ostéoradionécrose mandibulaire [7,9] 4 Extraction dentaire en territoire irradié [10] 2 Cystite hémorragique [11][12][13][14][15] 2 Rectite et entérite [3,18] 4 Lymphoedème [21] 4 Plexite [22] 4 Séquelles cutanées [23] 4 Douleurs [12,14,18,22,23] 4 Lésions neurologiques [25,26] 4 guérison de l'ostéoradionécrose mandibulaire à 1 an, n'était pas statistiquement différent entre les deux groupes (32 % de guérison dans le bras placebo, contre 19 % dans le bras oxygénothéra-pie hyperbare, risque relatif = 0,60, p = 0,23). Le protocole atypique d'oxygénothérapie hyperbare (deux séances par jour) et la défini-tion peu précise de l'ostéoradionécrose dans cet essai compliquent l'interprétation ces résultats.…”
Section: Indicationsunclassified
See 3 more Smart Citations
“…Ostéoradionécrose mandibulaire [7,9] 4 Extraction dentaire en territoire irradié [10] 2 Cystite hémorragique [11][12][13][14][15] 2 Rectite et entérite [3,18] 4 Lymphoedème [21] 4 Plexite [22] 4 Séquelles cutanées [23] 4 Douleurs [12,14,18,22,23] 4 Lésions neurologiques [25,26] 4 guérison de l'ostéoradionécrose mandibulaire à 1 an, n'était pas statistiquement différent entre les deux groupes (32 % de guérison dans le bras placebo, contre 19 % dans le bras oxygénothéra-pie hyperbare, risque relatif = 0,60, p = 0,23). Le protocole atypique d'oxygénothérapie hyperbare (deux séances par jour) et la défini-tion peu précise de l'ostéoradionécrose dans cet essai compliquent l'interprétation ces résultats.…”
Section: Indicationsunclassified
“…Elle est particulièrement fréquente après une radiothérapie prostatique ou postopératoire pour un cancer de l'endomètre [11]. Elle se caractérise par un syndrome irritatif et des hématuries, pouvant s'étaler sur les 2 à 10 ans suivant le traitement [11].…”
Section: Cystite Radique Hémorragiqueunclassified
See 2 more Smart Citations
“…Radiation cystitis frequently occurs following radiotherapy treatment for cervical, colorectal and prostate cancer, in addition to other pelvic tumors, with an incidence rate of ≤5% of all patients that undergo radiotherapy (1). Previous studies have reported that acute radiation cystitis, which typically develops 2-4 weeks after radiotherapy with a severity of <II [Radiation Therapy Oncology Group staging system (2)], occurs in 21-25% of all patients that undergo radiotherapy, while chronic radiation cystitis has an incidence rate of 1% (3).…”
Section: Introductionmentioning
confidence: 99%